Analysis of a Fault-Tolerant Module-Combined Stator Permanent Magnet Synchronous Machine - Bingyi Zhang; Baoping Gan; Qiaoshan Li (IEEE Access, 2020)
To solve the problems of large-size machining and complex control of fault-tolerant permanent magnet machines, a module-combined stator permanent magnet synchronous machine is proposed in this paper. The winding of the module-combined stator has two forms: large and small spans. The independent power supply of each module is adopted to decouple the electricity between each module, which enhances the manufacturing flexibility and the fault-tolerant ability of the motor. A mathematical model of the module-combined stator permanent magnet synchronous machine is established, and the design method of the machine is summarized. Then the analytical formula of the radial force acting on the stator under asymmetric operation is deduced. In addition, the torque-angle characteristics of the machine and the factors affecting the radial force are studied. Finally, the machine is prototyped, and both simulation and experiment are used verify the rationality of the proposed design.